Psychological Factors Associated With Chronic Migraine and Severe Migraine‐Related Disability: An Observational Study in a Tertiary Headache Center. Issue 4 (31st January 2017) - Seng, Elizabeth K.; Buse, Dawn C.; Klepper, Jaclyn E.; J. Mayson, Sarah; Grinberg, Amy S.; Grosberg, Brian M.; Pavlovic, Jelena M.; Robbins, Matthew S.; Vollbracht, Sarah E.; Lipton, Richard B.
Abstract : Objective: To evaluate the relationships among modifiable psychological factors and chronic migraine and severe migraine‐related disability in a clinic‐based sample of persons with migraine. Background: Evidence evaluating relationships between modifiable psychological factors and chronic migraine and severe migraine‐related disability is lacking in people with migraine presenting for routine clinical care. Methods: Adults with migraine completed surveys during routinely scheduled visits to a tertiary headache center. Participants completed surveys assessing chronic migraine (meeting criteria for migraine with ≥15 headache days in the past month), severe migraine disability (Migraine Disability Assessment Scale score ≥ 21), and modifiable psychological factors (depressive symptoms [Patient Health Questionnaire‐9], anxious symptoms [Generalized Anxiety Disorder‐7], Pain Catastrophizing Scale and Headache Specific Locus of Control). Logistic regression evaluated relationships between modifiable psychological factors and chronic migraine and severe migraine disability. Results: Among 90 eligible participants the mean age was 45.0 (SD = 12.4); 84.8% were women. One‐third (36.0%) met study criteria for chronic migraine; half of participants (51.5%) reported severe migraine‐related disability. Higher depressive symptoms (OR = 1.99, 95% CI = 1.11, 3.55) and chance HSLC (OR = 1.85, 95% CI = 1.13, 1.43) were associated with chronic migraine. Higher depressive symptoms (OR = 3.54, 95%CI = 1.49, 8.41), anxiety symptoms (OR = 3.65, 95% CI = 1.65, 8.06), and pain catastrophizing (OR = 1.95, 95% CI = 1.14, 3.35), were associated with severe migraine‐related disability. Conclusions: Psychiatric symptoms and pain catastrophizing were strongly associated with severe migraine‐related disability. Depression and chance locus of control were associated with chronic migraine. This study supports the need for longitudinal observational studies to evaluate the relationships among naturalistic variation in psychological factors, migraine‐related disability, and migraine chronification.